Engineering of a modular and synthetic phosphoketolase pathway for photosynthetic production of acetone from CO2 in Synechococcus elongatus PCC 7942 under light and aerobic condition - Chwa Jun Won; kim wook-jin; Sim, Sang Jun; Um, Youngsoon; Woo, Han Min (Blackwell Publishing Inc., 2016)
Capture and conversion of CO2 to valuable chemicals is intended to answer global challenges on environmental issues, climate change and energy security. Engineered cyanobacteria have been enabled to produce industry-relevant chemicals from CO2. However, the final products from cyanobacteria have often been mixed with fermented metabolites during dark fermentation. In this study, our engineering of Synechococcus elongatus PCC 7942 enabled continuous conversion of CO2 to volatile acetone as sole product. This process occurred during lighted, aerobic culture via both ATP-driven malonyl-CoA synthesis pathway and heterologous phosphoketolase (PHK)-phosphotransacetylase (Pta) pathway. Because of strong correlations between the metabolic pathways of acetate and acetone, supplying the acetyl-CoA directly from CO2 in the engineered strain, led to sole production of acetone (22.48mg/L +/- 1.00) without changing nutritional constraints, and without an anaerobic shift. Our engineered S.elongatus strains, designed for acetone production, could be modified to create biosolar cell factories for sustainable photosynthetic production of acetyl-CoA-derived biochemicals.